Impact of digital technology on the efficiency of high-standard farmland construction: evidence from China - Wei Zhang (Frontiers in Sustainable Food Systems)
High-standard farmland construction (HSFC) is a key measure to ensure national food security. The development of digital technology has brought new opportunities for HSFC. Based on panel data from 30 provinces (municipalities and autonomous regions), this paper employs a two-way fixed effects model, a panel threshold model, and a spatial Durbin model (SDM) to empirically examine the impact of digital technology on HSFC efficiency, as well as its threshold and spatial spillover effects. The study yielded the following key findings: First, digital technology has significantly improved the efficiency of HSFC. Simultaneously, its positive impact is more pronounced in areas with smaller terrain undulations, areas with higher agricultural land transfer, and eastern regions. Second, the impact of digital technology on the efficiency of HSFC exhibited a double threshold effect. When the level of digital technology is below the second threshold, it will significantly affect the efficiency of HSFC, and when the level of digital technology is between the first threshold and the second threshold, it will significantly affect the efficiency of HSFC. The effect is particularly strong when digital technology falls between the first and second thresholds. Third, digital technology has generated significant negative spatial spillover effects on the efficiency of HSFC. Based on this, we should strengthen the construction of rural digital infrastructure, build a digital management system for HSFC, and at the same time promote regional coordinated development of HSFC to achieve efficiency improvement in HSFC.